Developing a typology of models of palliative care delivery in prisons in high-income countries: protocol for a scoping review with narrative synthesis. Issue 4 (29th April 2022) - Gilbert, Emma; Turner, M; de Viggiani, Nick; Selman, Lucy
Abstract : Introduction: A combination of punitive sentencing practices within ageing populations, compounded by the health challenges faced by people in prison, means that dedicated palliative care provision within prisons is a pressing requirement. However, evidence about exactly how quality palliative and end-of-life care is delivered in this environment remains sparse. This review aims to develop a typology of models of palliative and end-of-life care delivery within prisons in high-income countries to inform service development and policy. Methods and analysis: We will conduct a scoping review of published studies and grey literature, following the Arksey and O'Malley framework. We will report data on models of palliative and end-of-life care delivery in prisons in high-income countries. Searches will be undertaken in Medline, EMBASE, CINAHL, Social Sciences Citation Index and PsyINFO for all study types, published from 1 January 2000 to December 2021, and reference lists from key reviews and studies will be screened for additional references. We will also screen grey literature from within other high-income countries using a targeted search strategy. For published reports of original research, study quality and risk of bias will be assessed independently by two reviewers using the Mixed Methods Appraisal Tool. A narrative synthesis of the data will be undertaken, integrating the results of the quality assessment. Ethics and dissemination: Approval by research ethics committee is not required since the review only includes published and publicly accessible data. We will publish our findings in a peer-reviewed journal as per Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidance. Protocol registration: The final protocol was registered with the Research Registry on 26 November 2021 (www.researchregistry.com ). Unique ID number: reviewregistry1260.